Development of Live-Worksheets Technology based on the Problem Based Learning model in the Horeg Sound Wave Phenomenon - Rahmatta Thoriq Lintangesukmanjaya; Oktamia Ramadhani; Dwikoranto Dwikoranto; Noval Maleakhi Hulu (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: Developing interactive Live-Worksheets based on Problem-Based Learning (PBL) on physics material with a contextual phenomena approach. Method: This research is a Research and Development (RnD) study. This type of research uses the 4D method, which includes four stages: define, design, develop, and disseminate.  Results: The results of developing live-worksheet technology based on the Problem-Based Learning model with the sound horeg phenomenon have proven to be valid and practical. The implementation of digital technology-based live worksheets using a problem-based learning model has been proven to increase student learning independence and enthusiasm through real-world phenomena such as sound waves. Looking ahead, the integration of intelligent technologies such as AI, VR, and virtual simulations has the potential to strengthen interactive, contextual, and practice-oriented physics learning. Novelty: The integration of technology and problem-based learning models can encourage students to generate new ideas from the problems presented. The use of AI technology in integrated learning media is crucial, and innovation in ethnoscience approaches is needed.